The influence of higher order thinking and metacognitive skills towards hands-on teaching among primary school science teachers - Sulaiman, Tajularipin; Subramaniam, Punnithann; Kamarudin, Nurzatulshima (Human Resource Management Academic Research Society, 2019)
Higher order thinking skills and metacognitive skills are essential skills in acquiring knowledge in today’s challenging world. This study examined the influence of higher order thinking and metacognitive skills on hands-on teaching in science among primary school Science teachers. The first objective of this study is to determine the level of higher order thinking and metacognitive skills among science teachers. The second is to examine the relationship between higher order thinking and metacognitive skills on hands-on teaching in science. The study used descriptive and correlation design. The findings of the descriptive analysis showed that the level of higher order thinking skills is high (M = 4.36, S.D. = 0.577) among science teachers. In addition, the findings show that metacognitive skill level was also high (M = 4.39, S.D. = 0.579). Next, the level of hands-on teaching in science is high (M = 4.37, S.D. = 0.543) among the science teachers. The findings show that there is a significant relationship between higher order thinking skills and hands-on teaching in science (r = 0.739, n = 94, p < 0.01). Besides, there is a significant relationship between metacognitive skills and hands-on teaching in science (r = 0.826, n = 94, p < 0.01). There was a stronger relationship between metacognitive skills to hands-on teaching than higher order thinking skills. Multiple regression analysis was conducted to observe the influence and the findings showed that the Beta value for metacognitive skills is higher (0.626) compared to the Beta value of higher order thinking skills (0.265). This indicates that metacognitive skills have more influence on hands-on teaching among the primary school science teachers. This study suggests that science teachers need to focus more on higher order thinking skills (HOTS) and metacognitive teaching.